'Heat transfer at low temperature in the entry section of a solid propellant rocket nozzle' - Smith, A. G. (College of Aeronautics, 1962)
Heat transfer in the converging section of the nozzle of a simulated solid propellant rocket with a star-shaped conduit has been investigated in the following way: (a) Area-average heat transfer has been measured on a room temperature rig, with and without a simulated charge. (b) Theoretical heat transfer has been calculated without the charge (axisymmetric laminar flow). (0) An attempt has been made to predict the detailed distribution of heat transfer by measurements of mass transfer on a nozzle made of napthalene. (d) Flow visualisation has been performed on a water-rig … [cont.].